Influence of cognitive processes on driver decision-making in dilemma zone - Robert Kaul; Meike Jipp (Transportation Research Interdisciplinary Perspectives, 2023)
In the past, research, which addressed driver behaviour in dilemma zone while approaching signalised intersections, did not focus on cognitive processes underlying stop/go decisions and collision risk after yellow-onset. Therefore, a study in a dynamic driving simulator with 20 participants was conducted to examine cognitive processes as basis of decision-making at signalised intersections. The study followed a 2×2 design with repeated measures. First, cognitive processes were triggered by perceptual cues, like the onset of yellow and a car in a leading position. Second, a cognitive distracting secondary task, the drivers had to solve interfered with cognitive processes. The results show, that a car in a leading position increases the probability not to stop after yellow-onset. Furthermore, the cognitive distracting secondary task leads to longer perception-response times (PRT) after yellow-onset, but only if there was no car in a leading position. Additionally, pupillary responses of the drivers during cognitive loading driving conditions are supporting this pattern of results. Finally, the concept of coupled motion is suggested to explain the underlying stop/go pattern of drivers after yellow-onset.